2004
DOI: 10.1111/j.1524-4741.2004.09614.x
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Response of Choroidal Metastases from Breast Cancer to a Combination of Trastuzumab and Vinorelbine

Abstract: We report the case of a 57-year-old woman with unilateral choroidal metastases from HER-2-positive breast cancer. She was given trastuzumab and vinorelbine with complete resolution of her visual defect after one cycle of treatment. This article illustrates that treatment using trastuzumab-containing chemotherapy regimens in HER-2-overexpressing breast cancer patients with choroidal metastases may be an alternative therapeutic strategy to initial orbital irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…One case report reported a complete response following trastuzumab [39]. Overall, the tumor response rates with systemic treatments appear worse than with EBRT suggesting not to omit radiation therapy.…”
Section: Tumor-specific Systemic and Multimodal Treatmentsmentioning
confidence: 92%
See 1 more Smart Citation
“…One case report reported a complete response following trastuzumab [39]. Overall, the tumor response rates with systemic treatments appear worse than with EBRT suggesting not to omit radiation therapy.…”
Section: Tumor-specific Systemic and Multimodal Treatmentsmentioning
confidence: 92%
“…Other local treatments like photodynamic therapy, laser, intravitreal injection of antiangiogenic drugs have also been used [34][35][36][37][38][39][40][41]. Photodynamic therapy with verteporfin (which specific target is the vascular endothelium) leads to destroy the tumor by direct effect (mediated by singlet oxygen), vascular damage and autoimmune response activation.…”
Section: Other Local Treatmentsmentioning
confidence: 99%
“…23 In two reports trastuzumab in combination with other systemic therapies led to the regression of choroidal metastases within 1–2 months. 47,69 Cardiac dysfunction was seen in 3–7% of patients enrolled in clinical trials of trastuzumab alone, but 75% of these patients improved with treatment for congestive heart failure. 57 …”
Section: Systemic Therapiesmentioning
confidence: 99%
“…35,53,58 Several case reports, including our patient with NSCLC, have shown that with the addition of new biologic agents and hormone therapies, patients may respond within a reasonable time period on systemic therapy alone. 40,47,69 …”
Section: Systemic Therapiesmentioning
confidence: 99%
“…As in the presented cases, most patients with ocular metastases due to breast cancer suffer from metastases at other locations as well; therefore, a systemic treatment is indicated for most of the patients. Recently, one case of dramatic local response of a unilateral choroidal metastasis in Her2/neu-positive breast cancer to systemic therapy with trastuzumab and vinorelbine was reported (Wong et al 2004). If patients receive systemic treatment and there is no rapid progress concerning the ocular metastases, it might thus be possible to await a local effect.…”
Section: Discussionmentioning
confidence: 97%